Perubahan Perilaku Kesiagaan Bencana melalui Penggunaan Media Android-Based Digital Radio pada Mahasiswa Poltekkes Kemenkes Padang - Widdefrita, Widdefrita; Amos, John; Pratiwi, Mutiara Ika (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2023)
Background. Socialization of knowledge, attitudes and behavior of disaster preparedness is a learning process. Stages can be developed in the learning process of disaster preparedness through android-based digital radio media. The initial survey in 2020 in the health student environment found that 55% had low knowledge, while 89% of students had a poor attitude towards disaster preparedness. Objective. This study aims to determine changes in disaster preparedness behavior using Android-Based Digital Radio media for students of the Poltekkes Kemenkes Padang. Methods. This type of research is a mix method with qualitative and quantitative approaches. The population used was students of the Poltekkes Kemenkes Padang, the sample was taken using the Non-Random Sampling method with Purposional Sampling techniques from each Department / Prodi. Qualitative research uses radio, BPBD, Information of Technology (IT) expert informants. Data collection using google form questionnaires and interview guidelines. Data processing was carried out using SPSS in univariate and bivariate with the Wilcoxon test. Results. The study showed that students' knowledge of disaster preparedness before using android-based digital radio media with an average of 12.69 increased to 13.98. Student attitudes towards disaster preparedness before using android-based digital radio media with an average of 41.64 increased to 43.83. The results showed that there was an effectiveness of android-based digital radio on knowledge (P=0.0001) and attitudes (p=0.0001).